(untitled) (Quaestiones Disputatae: temas en debate, 2025)
The aim of this paper is to present the introduction to “The ecological crisis as a crisis of sensitivity” from the book Ways of Being Alive by Baptiste Morizot. In it, the author attempts to demonstrate that the current ecological crisis is a crisis of sensitivity among modern men and women towards living beings and the planet. The legacy of our modernity has reduced other living beings to an existence of lesser value. This conception has broken our relationship with living things. This cosmic loneliness has become the anthroponarcissistic “closed room” that has isolated human beings.